Peningkatan Pengetahuan pada Pasien Hipertensi Melalui Edukasi - Oktaviana, Elisa; Rispawati, Baik Heni (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Hypertension is a public health problem in the world, both in developed and developing countries. Hypertension is called the silent killer because it often becomes a killer without any complaints, so that sufferers do not know they have hypertension and are only discovered after complications occur. In the working area of ​​the Gangga Public Health Center, it shows that the people in Jugil hamlet who have less knowledge are 65% and those who have sufficient knowledge are 35%. The results of the community service activities that have been carried out in Jugil Hamlet, Sambik Bangkol Village, Working Area of ​​the Gangga Health Center on October 25 2022 using the lecture method where participants who were hypertension patients who attended totaled 41 people. There is a difference in the average knowledge before and after education where the knowledge obtained is increasing. Education has an influence on increasing the knowledge of hypertensive patients, this is very useful so that people know how to manage hypertension independently and reduce the occurrence of complications that can occur in hypertensive patients. So that the provision of education really needs to be done both for patients who experience non-communicable diseases and infectious diseases. Health workers should provide education about hypertension prevention so that public awareness and knowledge will increase